Sustainable leadership: power of influence in MNCS in Malaysia - Lo, May-Chiun; Thurasamy, Ramayah; Yin, Chai Wang (Routledge, 2015)
Building upon social exchange theory which explains how power is gained and lost in the process of influence between an agent and the target, this article hypothesized the impact of supervisors’ and subordinates’ power bases on the usage of influence tactics by the supervisors. Bases of power of supervisors, subordinates and influence tactics were conceptualized as seven-, seven- and nine-dimensional constructs, respectively. Three hundred and eighty-five pairs of Malaysian managers and executives working in large multinational companies participated. Currently, the manufacturing sector is considered as one of the cornerstone of Malaysia’s economic diversification strategy. The findings suggested that supervisors apply various influence tactics on their subordinates.